Analysis of unsteady radial forces of multistage centrifugal pump with double volute. Issue 3 (8th May 2018) - Cui, Baoling; Li, Xiaodi; Rao, Kun; Jia, Xiaoqi; Nie, Xiaolin
Abstract : Purpose: Radial vibration of horizontal centrifugal pump has a close association with radial exciting forces. The purpose of this paper is to analyze the unsteady radial force in multistage centrifugal pump with double volute in detail and investigate the relevance of static pressure, radial force and radial vibration. Design/methodology/approach: The unsteady numerical simulation with realizable k-ε turbulence model was carried out for a multistage centrifugal pump with double volute using computational fluid dynamics codes Fluent. The performance tests were conducted by use of a closed loop system and performance curves from numerical simulation agree with that of experiment. Vibration tests were carried out by vibration probes instrumented on the bearing cover of pump near no-driven end. Fast Fourier transform was used to obtain the frequency components of radial forces on the impellers from numerical simulation, which are compared with ones of radial vibration from experiment in Y and Z direction. And the static pressure distributions in the impeller were analyzed under different flow rates. Findings: The symmetrical double volute can effectively balance radial forces. The maximum radial force and vibration velocity appear at 0.6 Q among the three flow rates 0.6 Q, Q and 1.2 Q . The frequencies corresponding to relatively large amplitude of vibration velocities and radial forces on the impellers in Y direction are blade passing frequency of the impellers. Blade passing frequency of first-stage impeller and shaft frequency are predominating in Z direction. It indicates that the radial vibration of centrifugal pump is closely related to the unsteady radial force. Originality/value: The unsteady radial forces of the impeller in multistage centrifugal pump with double volute were comprehensively analyzed. The radial forces should be considered to balance during the design of multistage centrifugal pump.